Penerapan Penerapan Model Pembelajaran Kooperatif Think Pair Share Untuk Meningkatkan Kemampuan Berpikir Kritis Mata Pelajaran Pendidikan Agama Islam - Anuar, Khairul; Yupidus, Yupidus; S, Ayu Purnamasari (ANTHOR: Education and Learning Journal, 2023)
The research is shaped Research Action (PTK). Level of critical thinking ability of studentsto Islamic Religion Education subjects still low. This is seen in the learning process ofstudents' critical thinking skills, which is now working on worksheets or student evaluationshave not been able to bring their own ideas. To improve critical thinking of Islamic ReligionEducation subjects skills at SDIT Raudhaturrahmah Pekanbaru, fourth grade be applied modeling Think Pair Share Cooperative Learning. The Subjects in this research is in fourthgrade and the samples are 25 students. That will be the saurce data to take the data it usedthe observation activities of teacher and students, and student’s ability in critical thinking of Islamic Religion Education subject. The highest average student’s ability in critical in critical thinking of Islamic Religion Education subject in first cycle it’s only get 60%, highest and lowest is 8%. While in the second highest cycle is 88% and the lowest is 48%. From the first and second cycle it. Can be seen that the implementation of cooperative learning model think pair share. Can improve students ability in critical thinking of science subject, it can be concluded that the hypothesis of this research that if the model is applied Think Pair Share Cooperative learning can enhance students' critical thinking skills of Islamic ReligionEducation at fourth grade students of SDIT Raudhaturrahmah Elementary School Pekanbaru.